M03 Complete Huntingtin Haplotypes For Allele-specific Silencing. (17th September 2014) - Kay, C; Collins, J; Skotte, N; Southwell, A; DiPardo, A; Ross, C; Squitieri, F; Hayden, M
Abstract : Background: The CAG repeat expansion causing Huntington disease (HD) occurs on specific haplotypes of the HTT gene. In humans, at least 2300 polymorphisms occur across HTT and offer potential targets for allele-specific silencing of the mutant gene copy. The organisation of all HTT polymorphisms into gene-spanning haplotypes, and the portion of the patient population treatable by selective silencing of haplotypes specific for the CAG expansion, is unclear and needed to guide selective silencing strategies. Aims: Our study sought to identify all genetic variants occurring on the most common HD haplotypes, A1 and A2, and determine the frequency of these haplotypes among ethnically distinct HD patient populations. We additionally sought to demonstrate selective HTT silencing using novel HD-associated polymorphisms identified by this work. Results: Using whole-genome sequencing data from the 1000 Genomes Project, and direct genotyping of diverse HD patient cohorts from Canada, Sweden, France, and Italy, we assemble complete HD haplotypes for all known common variants (>5%) in HTT. The most common HD haplotype, A1, is uniquely defined by three transcribed polymorphisms; the second most common HD haplotype, A2, is uniquely defined by five intragenic polymorphisms. Using antisense oligonucleotides (ASOs) targeting a novel A1-defining polymorphism, we silence mutant A1 HTT mRNA and protein in patient-derived cells, maintaining wild-type HTT expression at untreated levels. A1 is heterozygous at highest frequency in Northern European patient populations, where HD is most common. Conclusions: Across populations of European ancestry, silencing the A1 haplotype may offer allele-specific therapy in approximately half of HD patients. Our results suggest that targeting the A2 haplotype would allow selective silencing in an additional quarter of patients. In combination, antisense reagents silencing A1 and A2 offer selective silencing of mutant HTT in >70% of HD patients.